Differential expression profiles and functional prediction of circRNA in mice with traumatic heterotopic ossification - Wang, Zheng; Yi, Xinzeyu; Liu, Yuhang; Liu, Qiaoyun; Li, Zonghuan; Yu, Aixi (Frontiers in Immunology, 2023)
Traumatic heterotopic ossification (HO) is an intractable sequela incited by inflammatory insult. To date, the exact molecular mechanisms of traumatic HO formation remain unclear. Recent studies have indicated that circular RNAs (circRNAs) participate in various human skeletal diseases. Although the formation of HO recapitulates many programs during bone development and remodeling, few data are available concerning whether circRNAs could participate in this pathological osteogenesis. Herein, a mice traumatic HO model was established by Achilles tenotomy and burn injury. Microarray assay was performed to analyze the circRNA expression profile in mice HO tissues and to investigate the relevant mechanisms. We demonstrated that 491 circRNAs were significantly differentially expressed in mouse HO tissues by a fold-change ≥ 2 and p-value ≤ 0.05. Among them, the expressions of 168 circRNAs were increased, while 323 were decreased. The expression levels of 10 selected circRNAs were verified successfully by qRT-PCR. Gene ontology (GO) analysis exhibited that these differentially expressed circRNAs (DE-circRNAs) participated in a series of cellular processes. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that multiple upregulated and downregulated pathways were closely related to the DE-circRNAs in HO mice. The circRNA-miRNA-mRNA networks were established and demonstrated that DE-circRNAs may be involved in the pathological osteogenesis of HO through the circRNA-targeted miRNA-mRNA axis. In conclusion, our study first demonstrated the expression profiles and predicted the potential functions of DE-circRNAs in mice traumatic HO, which may shed new light on the elucidation of mechanisms as well as provide novel potential peripheral biological diagnostic markers and therapeutic targets for traumatic HO.